Scanning Electron Microscopy and Magnetic Characterization of Iron Oxides in Suspended Sediments - Sudarningsih Sudarningsih; Satria Bijaksana; Widodo Widodo; Irwan Iskandar; Darharta Dahrin; Silvia Jannatul Fajar; Kartika Hajar Kirana; Raghel Yunginger (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2024)
River sediment is the product of a sedimentation process in the river environment that originates from the weathering of bedrock or erosion processes, organic materials, particles, or anthropogenic substances. Previous research shows the magnetic mineral content in the sediments of the Citarum River and its tributaries. Suspended sediment was collected from the Citarum River and its tributaries in West Java, Indonesia, for mineralogical and granulometric analysis. The aim of this research is to distinguish between magnetic mineral sources, a scanning electron microscope equipped with energy dispersive X-ray spectroscopy (SEM-EDX), and rock magnetism. The hysteresis parameter verifies that the XRD measurement results show that the main magnetic minerals in suspended sediments are ferrimagnetic minerals such as magnetite (Fe3O4). According to the results of the SEM-EDX investigations, the magnetic granules in the Citarum River and its tributaries derive from two distinct sources: pedogenic and anthropogenic. The Citarum River and its tributaries’ magnetic granules are generally octahedral or angular in shape, with broken corners, indicating a pedogenic origin